The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1152/physiolgenomics.00100.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E deficiency and metabolic deficits in neuronal ceroid lipofuscinosis described by bioinformatics

Abstract: The mnd mouse, a model of neuronal ceroid lipofusinosis (NCL), has a profound vitamin E deficiency in sera and brain, associated with cerebral deterioration characteristic of NCL. In this study, the vitamin E deficiency is corrected using dietary supplementation. However, the histopathological features associated with NCL remained. With use of a bioinformatics approach based on high-resolution solid and solution state 1H-NMR spectroscopy and principal component analysis (PCA), the deficits associated with NCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…The increase at 1 month may therefore reflect an up-regulation of lipid synthesis resulting from metabolic changes associated with lipid storage and degradation, known to accompany the NCLs. Alternatively, we have shown previously the degradation of NAA to be slower in a mouse model of Cln8 (15). In addition, NAA is commonly thought of as a biomarker for neuronal density (44) and, as such, decreases have previously been linked to neuronal cell loss in numerous experimental and clinical conditions (45)(46)(47).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The increase at 1 month may therefore reflect an up-regulation of lipid synthesis resulting from metabolic changes associated with lipid storage and degradation, known to accompany the NCLs. Alternatively, we have shown previously the degradation of NAA to be slower in a mouse model of Cln8 (15). In addition, NAA is commonly thought of as a biomarker for neuronal density (44) and, as such, decreases have previously been linked to neuronal cell loss in numerous experimental and clinical conditions (45)(46)(47).…”
Section: Discussionmentioning
confidence: 76%
“…In this present study we have applied a metabolomics approach to define biochemical abnormalities associated with a mouse model of juvenile NCL or Batten disease (14), which is caused by mutations in the Cln3 gene. Metabolic profiles derived from 1 H NMR spectroscopic analysis of biofluids and tissue extracts, in conjunction with multivariate statistics, have previously been demonstrated to be highly discriminatory for a number of neurological diseases, including a variant late infantile NCL (Cln8) (15). Using this approach, we have identified a number of metabolic deficits associated with this mouse model of juvenile NCL.…”
mentioning
confidence: 99%
“…Indeed a perturbation in glutamate/glutamine/GABA metabolism has previously been detected in a range of neurological disorders including a mouse model of variant late infantile NCL (CLN8), spinocerebellar ataxia 3, epilepsy and HuntingtonÕs disease (Behrens et al, 2002;Griffin et al, 2002Petroff et al, 2002;Burbaeva et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies using metabolic profiling to study CNS diseases examined brain extracts from two mouse models of Neuronal Ceroid Lipofuscinosis (NCL), the most prevalent form of paediatric neurodegeneration, associated with the CLN3 (MIM204200) and CLN8 (MIM 600143) loci (Griffin et al 2002;Pears et al 2005). Despite small samples size (n=5), metabolic profiling revealed that both NCL models displayed converging metabolic abnormalities.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Despite small samples size (n=5), metabolic profiling revealed that both NCL models displayed converging metabolic abnormalities. These abnormalities were even detectable at one month of age, before the animals expressed the neurological phenotypes (Griffin et al 2002;Pears et al 2005). MSEA highlighted alterations in D-glutamate and D-glutamine metabolism (Tab.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%